Using Chinese and First Nations philosophies about time and history to reimagine transcultural doctoral education. Issue 1 (2nd January 2023) - Manathunga, Catherine; Singh, Michael; Qi, Jing; Bunda, Tracey
ABSTRACT: Transcultural doctoral education has become a space to create opportunities for candidates to construct transcultural knowledge from the Global South. Rancière's ideas about the ignorant schoolmaster and the role of dissensus have created cosmopolitan pedagogies in doctoral education. However, the role of history in transcultural doctoral education remains unexplored and draws principally on Western theorists. This article explores Chinese and First Nations philosophies about time and history to reframe transcultural doctoral education. We argue that these philosophies can create spaces for innovative approaches to doctoral research. They can also rehumanise doctoral education and assist First Nations and transcultural doctoral candidates to connect their micro histories with macro cultural, cosmic understandings of what it means to be a researcher in the twenty-first century. This is vital if the dominant fast, linear timescapes of contemporary doctoral education are to be made more inclusive for First Nations and transcultural doctoral candidates.